2021
DOI: 10.1101/2021.03.19.21253661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of anti-PD1 response and resistance in clear cell renal cell carcinoma

Abstract: Antigen recognition and T-cell mediated cytotoxicity in clear-cell renal cell carcinoma (ccRCC) remains incompletely understood. To address this knowledge gap, we analysed 115 multiregion tumour samples collected from 15 treatment-naive patients pre- and post-nivolumab therapy, and at autopsy in three patients. We performed whole-exome sequencing, RNAseq, TCRseq, multiplex immunofluorescence and flow cytometry analyses and correlated with clinical response. We observed pre-treatment intratumoural TCR clonal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 137 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…Since multiregional molecular genetic studies have largely been performed without consideration of morphology, the investigation regarding the correlation between histologic immune status and underlying genomes has been limited [8]. Genetic analysis and multiplex immunofluorescence/immunohistochemical staining remain challenging in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Since multiregional molecular genetic studies have largely been performed without consideration of morphology, the investigation regarding the correlation between histologic immune status and underlying genomes has been limited [8]. Genetic analysis and multiplex immunofluorescence/immunohistochemical staining remain challenging in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently investigated this using paired longitudinal tumour and blood samples from patients with metastatic clear-cell renal cell carcinoma in a phase II study of first-line anti-PD-1 (nivolumab). 56 In bulk tumour samples, we showed that responders to nivolumab had significantly higher pre-treatment intratumour TCR clonality and cluster structure than non-responders, suggesting pre-existing adaptive immunity. Combining bulk and single-cell TCR and RNA-Seq data, we observed both novel and maintenance of pre-existing TCR clones in post-treatment samplesdbut only the latter correlated with ICB response.…”
Section: Source Of T Cells Driving Clinical Response To Icb Whether T...mentioning
confidence: 73%
“…Combining bulk and single-cell TCR and RNA-Seq data, we observed both novel and maintenance of pre-existing TCR clones in post-treatment samplesdbut only the latter correlated with ICB response. 56 Moreover, following treatment administration, we observed anti-PD-1 binds to both novel and pre-existing CD8þ T cells, but only pre-existing expanded TCR clones in responders had a cytotoxic phenotype (i.e. up-regulation of GZMB/K) and not in novel clones or in non-responder patients.…”
Section: Source Of T Cells Driving Clinical Response To Icb Whether T...mentioning
confidence: 74%
“…The authors suggested that nivolumab drives both maintenance and replacement of previously expanded T cell clones. Only maintenance correlated with response [22].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 91%
“…Translational data from other tumour entities such as melanoma support using immunotherapy with the tumour antigens in place to prime the immune response, [20,21] but it is unclear if this is also required in the setting of metastatic RCC. A recent publication including patients with synchronous clear-cell mRCC who were pre-treated with nivolumab and underwent either a biopsy or CN suggests that nivolumab maintains a pre-existing Tcell mediated immune response in the tumour tissue of patients responding to therapy [22]. A higher level of T cells was found in responders both pre-and posttreatment.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%